Pancasila Education Policy in Government Regulation Number 57 of 2021 concerning National Education Standards - Bramastia Bramastia; Arief Sadjiarto (Universitas Sebelas Maret, 2021)
The Pancasila education policy in Government Regulation Number 57 of 2021 concerning National Education Standards (SNP) must be revised. Pancasila must be a mandatory content in the Indonesian education system. Pancasila education in Indonesia in the reform era through the revision of Government Regulation Number 57 of 2021 concerning SNP cannot be separated from the national politics behind it.Educational reform through the revision of Government Regulation Number 57 of 2021 concerning SNP, in turn brings changes to the paradigmatic aspects of the study and learning of Pancasila education in Indonesia from the aspect of national education standardization. The objective of the Merdeka Belajar program is the profile of Pancasila students as an educational transformation. The introduction of Pancasila in the understanding and application of Pancasila is the main pillar of the transformation of Indonesian education which does not depend on a change of regime in power.